2017
DOI: 10.3389/fmicb.2017.01657
|View full text |Cite
|
Sign up to set email alerts
|

PCR and Omics Based Techniques to Study the Diversity, Ecology and Biology of Anaerobic Fungi: Insights, Challenges and Opportunities

Abstract: Anaerobic fungi (phylum Neocallimastigomycota) are common inhabitants of the digestive tract of mammalian herbivores, and in the rumen, can account for up to 20% of the microbial biomass. Anaerobic fungi play a primary role in the degradation of lignocellulosic plant material. They also have a syntrophic interaction with methanogenic archaea, which increases their fiber degradation activity. To date, nine anaerobic fungal genera have been described, with further novel taxonomic groupings known to exist based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
112
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 173 publications
6
112
0
1
Order By: Relevance
“…Anaerobic fungi of the phylum Neocallimastigomycota are effective fiber degrading organisms in the herbivore gut and have been reported to improve feed intake, feed digestibility, feed efficiency, and daily weight gain and milk production [39, 40]. Of the 50 most abundant OTUs, OTUs 14, 22, 25, 26, 31, 34, 35, and 45 were classified as members of the Neocallimastigomycota.…”
Section: Discussionmentioning
confidence: 99%
“…Anaerobic fungi of the phylum Neocallimastigomycota are effective fiber degrading organisms in the herbivore gut and have been reported to improve feed intake, feed digestibility, feed efficiency, and daily weight gain and milk production [39, 40]. Of the 50 most abundant OTUs, OTUs 14, 22, 25, 26, 31, 34, 35, and 45 were classified as members of the Neocallimastigomycota.…”
Section: Discussionmentioning
confidence: 99%
“…Within this consortium of anaerobic microbes, anaerobic fungi are the least well‐characterized, but they are some of the most active microbes against lignin‐infused substrates, containing the largest repertoire of biomass‐degrading genes in sequenced fungi . The low abundance of gut fungi in a rumen supplied with high‐starch diets, and conversely high abundance under high‐fiber conditions suggests that these fungi are highly adapted to fiber degradation, which is of particular interest for the hydrolysis of recalcitrant biomass encountered in bioprocessing . However, the first genomes of the anaerobic fungi were sequenced only in the past 5 years due to the problems associated with fungal culture, and difficulties that stem from AT‐richness and extensive genomic repeats .…”
Section: Introductionmentioning
confidence: 99%
“…21 While they can also produce lactate and ethanol as waste products, hydrogenosome-driven metabolism is likely more favorable. 11 identified cluster in a separate clade, which have been assigned to their own family (Neocallimastigaceae), order (Neocallimastigales), class (Neocallimastigomycetes), and phylum (Neocallimastigomycota). 23 They include three monocentric genera (Neocallimastix, Caecomyces and Piromyces) and three polycentric genera (Anaeromyces, Orpinomyces and Cyllamyces), with two additional proposed genera (Oontomyces and Buwchfawromyces) based on molecular data from other gut environments.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Comparative genomic studies have revealed that horizontal gene transfer appears to have played an important role in the adaptation of fungi to gut environments, which have included carbohydrate degrading enzymes as well as certain hydrogenosome enzymes. 11 Slowly, but surely, interest in anaerobic fungi has continued to gain in momentum, in large part driven by interest in their biotechnological potential. 11 With continued improvements in culturing, phylogenetic profiling, metagenomics, and gene annotation, more insights are likely yet to come for these fascinating fungi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation